2012
DOI: 10.1039/c2cc16878b
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole dendronised triphenylamines as solution processed high Tg amorphous hole-transporting materials for organic electroluminescent devices

Abstract: Carbazole dendrimers up to 4th generation were synthesized. They showed significantly high T(g), amorphous and stable electrochemical properties, and great potential as solution processed hole-transporting materials for OLEDs. Alq3-based green devices exhibited high luminance efficiency and CIE coordinates of 4.45 cd A(-1) and (0.29, 0.53), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 20 publications
0
51
0
Order By: Relevance
“…The morphological behavior of these dendrimers was monitored by DSC measurements. Only one endothermic peak due to glass transition was detected at 58 C with no crystallization or melting peaks observed when a powder of G1F3 was heated for the first run, implying that G1F3 was amorphous even when it was obtained directly from organic solvents [17]. This endothermic glass transition was detected again when the super-cooled sample was subsequently reheated.…”
Section: Thermal Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The morphological behavior of these dendrimers was monitored by DSC measurements. Only one endothermic peak due to glass transition was detected at 58 C with no crystallization or melting peaks observed when a powder of G1F3 was heated for the first run, implying that G1F3 was amorphous even when it was obtained directly from organic solvents [17]. This endothermic glass transition was detected again when the super-cooled sample was subsequently reheated.…”
Section: Thermal Propertiesmentioning
confidence: 94%
“…The HOMO energy levels were estimated from the onset potentials to be À5.33 and À5.29 eV for G1F3 and G2F3 respectively, according to the equation of HOMO (eV) ¼ À (E ox onset þ4.8 eV) [21]. Apparently the HOMO levels of these carbazole-based dendrimers are quite close to the work function of the ITO anode (À4.8~À5.0 eV) [17], implying that efficient hole injection at the anode/emitting layer interface could be expected when these dendrimers are used as the emitting layer of OLEDs. The energy band gaps (E g ) were determined by the absorption edge technique, and the LUMO levels were calculated by subtracting the gap from the energy of the HOMO [21].…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…All deuterated solvents were purchased from Cambridge Isotope Laboratories. The compounds of 1 [10],2 [11], 4 [12], 5 [13], 6 [14], and 7 [15] were prepared according to the modified literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Solution processes, such as spin coating or ink-jet printing, offer an attractive alternative approach in terms of the potential to enable low-cost and large area manufacturability that is more amenable to commercial interests [7]. Recently, some solution-processed small molecules have been demonstrated as good hole-transporting materials [8][9][10]. For example, Usluer et al reported a series of hole-transporting materials using dioctylfluorene, spirobi(fluorene) and spiro(cyclododecanefluorene) as core with different peripheral groups, which possessed high decomposition temperature (T d ) and T g values [11]; Promarak et al developed two bifunctional materials based on anthracene with the combined characteristics of deep blue light-emitting and hole-transporting ability [12]; Our group also reported a series of star-shaped compounds with the core of planar triphenylamine or hexakis (9,9-dihexyl-9H-fluoren-2-yl)benzene as solutionprocessed hole-transporting materials [13,14].…”
Section: Introductionmentioning
confidence: 99%